Development of a real-time mobile gamma-ray measurement system for shipboard use - Kim, Chang-Jong; Jang, Mee; Kim, Hyuncheol; Lim, Jong-Myoung; Lee, Wanno; Cho, Gyu-Seong (Nuclear engineering and technology, 2023)
Large areas must be rapidly screened to monitor radiation in marine environments. For this purpose, this study developed a mobile real-time gamma-ray measurement system for shipboard use and evaluated its performance. The system was developed to measure engine or generator cooling water by installing a canister inside the ship. The minimum detectable activity of the system is about 0.8 Bq/L for a 60 s measurement period, and real-time data transmission and remote control are possible. The system was tested in the field and is currently being installed and operated on ships in service. Such a ship-based real-time gamma-radiation measurement system is suitable for a wide range of marine radiation surveillance applications and is expected to be rapidly deployed.